The acceptance of Vegetables Certification Scheme (VCS) by members of Area Farmers Organization (AFO) of Serian / Su’udi Arof - Arof, Su’udi (2008)
This paper attempts to study the acceptance of a scheme, known as the 'VEGETABLE CERTIFICATION SCHEME (VCS), where farmers are registered with Department of Agriculture in order to produce pesticide-safe vegetables They have to follow an auditable code ofpractice on pesticide usage on theirfarms and the Department would monitor their farms periodically to check on their credentials. A certificate is issued annually subject to thefarmers being able to satisfy all. the conditions specified under the scheme.